Textbook of neonatal resuscitation - Bloom, Ronald S. [ (Ronald Samuel)] , 1938-; Kattwinkel, John (American Academy of Pediatrics, 2011)
"The extensively revised and updated 6th edition of the Neonatal Resuscitation Program (NRP) textbook and accompanying DVD-ROM are designed in accord with the program's curriculum changes and sharpened focus on active,hands-on learning. The text facilitates the newly recommended self-paced learning approach. Self-study is optimized to help students prepare for the mandatory online examination that replaces the traditional written test. It also complements the simulations and case-based sceanarios at the heart of the new NRP. Content updates thoughout the text and DVD-ROM reflect the 2010 American Academy of Pediatrics (AAP)/American Heart Association Guidelines for Neonatal Resuscitation. Must-know new material includes the latest recommendations across key areas of change including: Revisions in the NRP flow diagram; elimination of evaluation of amniotic fluid in initial rapid assessment; use of supplemental oxygen during neonatal resuscitation; use of pulse oximetry; chest compression procedures. The book includes a companion DVD-ROM (for use on both PC and Mac), bringing ahigher level of interactivity to the learning process. Active learning features on the DVD include multi-decision point scenarios and randomly generated clinical problems and outcomes"--P. 4 of cover